RELATIONSHIP BETWEEN THREE CONTEXT FACTORS AND FOOD BEHAVIOR OF STUDENTS IN PUBLIC UNIVERSITIES IN EDO STATE - Uwameiye, B.E.; Uwameiye, Raymond (International Journal of Research -GRANTHAALAYAH, 2019)
This paper examined the relationship between three context factors and food behavior of students in public universities in Edo State, Nigeria. The study was an ex-post facto research design adopting correlation approach. A sample of 956 students participated in the study. Three research questions and corresponding hypotheses guided the study. A self structured 43 item questionnaire was administered for data collection. The Mean, Standard deviation and Pearson Product Moment Correlation (PPMC) was used to establish the relationship between the variables. Findings revealed that: there is a significant relationship between personal factors and eating behavior of students in public universities in Edo State (r.062; P<.05); there is a significant relationship between school environment factors and eating behavior of students in Edo State (r.078; P<.05); and there is a significant relationship between peer factors and eating behavior of students in Edo State (r.076: P<.05). This paper recommends that it is of essence to give nutrition education a place in the curriculum of the university school system amongst other recommendations.